“Estudio comparativo de cuatro niveles de fertilización química nitrogenada y su efecto en el rendimiento de 03 variedades y 02 líneas promisorias de arroz, en la E.E.A el porvenir-Juan Guerra- San Martín” - Isuiza Salas, Mick Aldo (2015)
The present research work developed in the fields of investigation of the National Program of Rice - E.E.A "The Future" - INIA - Juan Guerra, with the target to determine the physiological, productive and economic effects of four levels of nitrogenous chemical fertilization, in three local varieties (INIA 507 - The Conquest, INIA 509 - The Hope, IDAL 186 - Fortress) and 02 promissory lines of rice of the INIA (CT18141-6-4-2-4-4-1-M I Ph-06 and CT18141-6-4-2-4-4-1-M I Ph-10), using dese of 160, 180, 200 and 220 Kg of N.ha-1 , with urea as nitrogenous source. The study was realizad using a blocks design completely at random with an arrangement factorial of 5 x 4, with four repetitions. Based on the realizad statistical analyses, the varieties in study, they had significant answers to the application of the nitrogen; standing out significantly the variety The Hope who obtained a better yield with regard to other varieties in study with dose of 180 Kg of N.ha-1 in an average of 9266.75 Kg ha-1 . High doses of nitrogen (200 and 220 Kg N.ha-1), increased the incidence of White Sheet in the rice varieties, being the variety IDAL 186 - Fortress, which presentad the highest index of macolles affected 3,36 %. With regard to the capacity of macollamiento the variety INIA 507 - The Conquest showed a better behavior at the different applied levels of nitrogen (160, 180, 200 and 220 Kg of N.ha-1), overcoming to other varieties in study. The studied nitrogen doses did not influence the mill's quality (% of entire grain), but if there was difference between varieties, standing out again the variety INIA 509 - The Hope together with the variety Fortress. Keywords: Nitrogen fertilization, Varieties, Promising lines, Rice. ANEXO